Searching for rich stories in Rich Pictures: Analysing visual stories about living with cancer - Emily R. E. Evans; Niels van Poecke; Hanneke W. M. van Laarhoven; Esther Helmich (PLoS ONE, 2026)
Stories play an important role in making meaning of illness experiences and (re)establishing self-identity. Yet, telling and investigating stories about living with incurable cancer may be challenging, as people may perceive their illness experiences as hard to communicate. Visual research methods are increasingly employed to tell stories about illness. Rich Pictures (RPs) – hand-drawn, visual stories – stand out due to their ability to visualise and investigate multidimensional illness stories in a single snapshot and, when repeatedly used, their construction over time. RPs therefore present opportunity in investigating the construction of stories about life with an incurable disease. However, RP analysis methods often prioritise the accompanying verbal narratives, and practical guidance for the analysis of RPs themselves remains scarce. This may overlook the valuable contributions RPs can have in understanding illness narratives. As such, we developed a multi-level, systematic analysis process for RPs themselves, i.e., without the analysis of interviews, as stories of life with incurable cancer. Our method comprises a core analytical level – a six-step, systematic coding process, with two ‘extensions’ for comparisons of RPs across different timepoints and groups. This is supported by ‘gallery walks’ – a participatory approach to visual analysis. In doing so, we forward our method and the epistemic richness of analytically engaging with RPs as valuable to research on the ways people living with incurable cancer (re)create their stories, and in research contexts beyond.